Shape and Meaning of Banyumasan Batik Motif: A Study in The Context of Finding Cultural Identity - Esa Yulianto, Robin; Triyanto, Triyanto; Rokhmat, Nur (Catharsis, 2020)
Banyumasan batik is one of the original cultural products from Banyumas Regency which has its own aesthetic shape and distinctive meaning as one of the identities of the Banyumas community. This study aims to analyze the aesthetic shape of Banyumasan batik, the meaning of Banyumasan batik by batik craftsmen, and to construct cultural identity through Banyumasan batik. The study was conducted by using qualitative methods with interdisciplinary socio-cultural studies and arts (fine arts), the data collection was conducted by observation, recording, interviews and documents. The analysis of art data used the theory of aesthetic shape, cultural symbols, and cultural identity. First, the aesthetic shape of Banyumasan batik motif has distinctive and varied ornaments. Second, the meaning of the craftsmen of batik produces iconic and symbolic meanings that reflect the community, natural and physical environment, and culture of Banyumas. Third, the aesthetic shape and the meaning of Banyumasan batik motif are interrelated and support to be used as the cultural identity of the Banyumas community. The results of this study can be used as a reference source for batik craftsmen in the creation of batik motif, as well as sources and media for learning art and culture formally and informally, namely in schools and in the community about Banyumasan batik.